CARBON EMISSION ACROSS MANY SPECTRUMS USE IN MULTI-INCOME GROUPS COUNTRIES IN THE WORLD - Danny Ivan Rantung; Nouke Sysca Oroh; Ika Prayanthi (Jurnal Ekonomi, 2022)
The purpose of the study is to determine specifically examine the quadratic impact of economic growth, consumption of renewable and non-renewable energy, depletion of natural resources, and population levels in all countries in the world which are grouped into 4 income groups namely high-, low-, middle- and upper-income groups. and lower middle. The data used in this study is panel data from all countries in the world for 29 years from 1990 to 2018 with 6 variables. The model has been developed and the instrument used in this research is STATA version 14.  Regression result show that for countries in the low, upper middle and lower middle-income groups, the results are significant for square of economic growth contributes to the increase in the amount of carbon dioxide emissions. Consumption of non-renewable energy for countries in the high- and low-income groups were significant to the amount of carbon dioxide emissions. Consumption of renewable energy in all income groups of countries in the world, the correlation between increased consumption of renewable energy and total carbon dioxide emissions is negative with significant alpha value.  Increasing deforestation has a negative correlation with the amount of carbon emissions. Countries in the high- and low-income groups were found to be significant and countries in the upper and lower middle-income groups were not significant.